2023
DOI: 10.1186/s43014-023-00162-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in mass transfer and fluid flows in non-thermal food processing industry – a review

Abstract: All around the world, food processing techniques make use of various kinds of treatments to improve the shelf-life of foods. The commonly used thermal treatments are likely to result in deteriorating the sensory as well as nutritional qualities of foods. However, consumers are now demanding for safer and cleaner food without needing to compromise on the quality. Owing to the evolving nature of consumer demands, food technologists and others in the agro-food chain have devised processes to meet these changing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…This was attributed to the single frequency-treated generated standing waves, which impacted the range of its action less uniformly than that of the multiple frequency ones [33]. However, employing a low-frequency range of 20-50 kHz has been recommended to achieve optimal process and productivity due to such frequencies' enhanced mass transfer and cell permeability [34,35]. Therefore, this study indicated that the UAOD treatment with multiple frequencies (40/80 kHz) contributed to the enhancement of the SG rate performance of the pineapple slices.…”
Section: Frequencymentioning
confidence: 99%
“…This was attributed to the single frequency-treated generated standing waves, which impacted the range of its action less uniformly than that of the multiple frequency ones [33]. However, employing a low-frequency range of 20-50 kHz has been recommended to achieve optimal process and productivity due to such frequencies' enhanced mass transfer and cell permeability [34,35]. Therefore, this study indicated that the UAOD treatment with multiple frequencies (40/80 kHz) contributed to the enhancement of the SG rate performance of the pineapple slices.…”
Section: Frequencymentioning
confidence: 99%